Promoting productive thinking and physics learning achievement of high school students through STEAM education - Piyathida Polmart; Prasart Nuangchalerm (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
Through STEAM education, this action research aims to improve senior high school students' ability to think critically and learn effectively. The target group for this study consisted of 36 senior high school students from one school in Thailand. A STEAM education lesson plan, a test of productive thinking, and a test of learning achievement were used as research tools. Statistics tools including mean, standard deviation, and percentage were used to analyze the data. The study showed that throughout the first and second cycles, students had scored 51.16% and 65.15% on the productive thinking scale respectively. The learning organization improved the academic performance of the students in each cycle. It is reasonable to infer and consider the potential that STEAM education can support students' intellectual development. It is useful for scientific instruction in schools, but teachers also need to be knowledgeable about how to organize their classes.